Utility of the occupation-centered intervention assessment in pediatric occupational therapy practice: Journal of Occupational Therapy, Schools, & Early Intervention. Issue 3 (3rd July 2022) - Hinkley, Emily; Leach, Christen; Jewell, Vanessa D.; Wienkes, Taylor L.
ABSTRACT: Best practice supports the use of occupation as a therapeutic agent of change for pediatric occupational therapy practice. However, limited tools to promote the development of and implementation of occupation-centered practice exist. This study explored the clinical utility of the Occupation Centered Intervention Assessment (OCIA) as a tool to facilitate occupation-centered practice in outpatient and school-based pediatric settings. The OCIA allows practitioners to reflect on their own practice by scoring interventions on personal, contextual, and occupational relevance. This qualitative, descriptive study utilized semi-structured interviews (n = 12) with practitioners in outpatient and school settings to glean information regarding tool utility. A six-step thematic analysis process guided the coding process. Four themes emerged from the data related to clinical utility of the OCIA: reflection on practice habits, practice settings influence therapy service delivery, translation of theoretical knowledge into practice technique, and the distinct value of occupation. Preliminary evidence supports the use of the OCIA in outpatient and school pediatric settings to promote reflection on occupation-centered practice for students and novice practitioners, although some setting are more conducive to use of an occupation-centered approach than others.